A global survey of ergonomics practice patterns and rates of musculoskeletal pain among urologists performing retrograde intrarenal surgery - TANIDIR, YILÖREN (My University, 2022)
Purpose: Retrograde intrarenal surgery (RIRS) requires urologists to adopt an awkward body posture for long durations. Few urologists receive training in ergonomics despite the availability of ergonomic best practices utilized by other surgical specialties. We characterize ergonomic practice patterns and rates of musculoskeletal (MSK) pain among urologists performing RIRS.Methods: A web-based survey was distributed through the Endourological Society, the European Association of Urology, and social media. Surgeon anthropometrics and ergonomic factors were compared with ergonomic best practices. Pain was assessed with the Nordic Musculoskeletal Questionnaire (NMQ).Results: Overall, 519 of 526 participants completed the survey (99% completion rate). Ninety-three percent of urologists consider ergonomic factors when performing RIRS to reduce fatigue (68%), increase performance (64%), improve efficiency (59%), and reduce pain (49%). Only 16% received training in ergonomics. Residents/fellows had significantly lower confidence in ergonomic techniques compared with attending surgeons with any career length. Adherence to proper ergonomic positioning for modifiable factors was highly variable. On the NMQ, 12-month rates of RIRS-associated pain in >= 1 body part, pain limiting activities of daily living (ADLs), and pain requiring medical evaluation were 81%, 51%, and 29%, respectively. Annual case volume >150 cases (odds ratio [OR] 0.55 [0.35-0.87]) and higher adherence to proper ergonomic techniques (OR 0.67 [0.46-0.97]) were independently associated with lower odds of pain. Limitations include a predominantly male cohort, which hindered the ability to assess gender disparities in pain and ergonomic preferences.Conclusions: Adherence to ergonomic best practices during RIRS is variable and may explain high rates of MSK pain among urologists. These results underscore the importance of utilizing proper ergonomic techniques and may serve as a framework for establishing ergonomic guidelines for RIRS.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Nephrology; ÜROLOJİ VE NEFROLOJİ; Klinik Tıp; Klinik Tıp (MED); UROLOGY & NEPHROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Üroloji; Urology; ergonomics; retrograde intrarenal surgery; musculoskeletal pain; MINIMALLY INVASIVE SURGERY; PHYSICAL DISCOMFORT; GUIDELINES; SYMPTOMS